Supportive principal leadership and learning quality: the mediating role of teachers’ affective commitment - Dede Mardanil; Anisah Anisah; Lusi Susanti; Jasrial Jasrial (Journal of Educational and Learning Studies, 2026)
This study aimed to analyze the effects of supportive principal leadership on teachers’ affective commitment and learning quality, as well as the mediating role of teachers’ affective commitment in public elementary schools in Kinali District. This study employed a quantitative correlational design using Structural Equation Modeling (SEM). The population consisted of 386 public elementary school teachers, with 196 respondents selected through proportional stratified random sampling. Data were collected using validated and reliable Likert-scale questionnaires measuring supportive principal leadership, teachers’ affective commitment, and learning quality. The findings showed that supportive principal leadership significantly influenced teachers’ affective commitment (β = 0.73; CR = 6.84; p < 0.001) and learning quality (β = 0.41; CR = 4.12; p < 0.001). Teachers’ affective commitment also had a significant positive effect on learning quality (β = 0.52; CR = 5.36; p < 0.001). Indirect analysis revealed that supportive leadership affected learning quality through teachers’ affective commitment with an indirect effect of 0.38 and a total effect of 0.79. The SEM model demonstrated good fit indices (RMSEA = 0.041; CFI = 0.96; TLI = 0.95). Supportive principal leadership and teachers’ affective commitment play significant roles in improving learning quality in elementary schools.